(untitled) (Research, Society and Development, 2021)
The objective of this study was to realize the pharmaceutical service of health tracking of the metabolic syndrome (MS) in servers of a Public University in Belém-PA.The study was a cross-sectional descriptive, composed of servers of both sexes aged between 20 and 74 years, from the collection of sociodemographic and cardiometabolic data and measurement of abdominal circumference (AC) for evaluation of central obesity (CO). MS was characterized by the aggregation of at least 3/5 components, which are: fasting hyperglycemia, hypertriglyceridemia, high-density lipoprotein (HDL-c) hypolipidemia, arterial hypertension (AH) and CO. For the statistical analysis, the GraphPad Prism® - 5.00-Windows software was used, with Pearson’s Correlation Coefficient for sample analysis; Chi-square test for analysis of the presence/absence of MS x Framingham strata; Fisher’s Exact Test to evaluate the relative risk. The results showed a mean age of 46±13 years and a majority of women (60.4%) within the sample of 91 servers. There was a predominance of low HDL-c levels (73.6% and p=0.0165); of CO (53.8% and p<0.0001) and AH (50.5%). Among the employees, 48.3% were classified as "Presence of MS", among which there was a predominance in the medium (69.2%) and high (82.6%) strata. Those classified as "Absence of MS" were predominant in the low-risk stratum (70.9%). The analyses of cardiovascular risk x MS (p<0.0001) and age x MS (p<0.0002) were directly proportional. A high percentage of servers classified as "Presence of MS" was perceived, and the screening proved to be effective in the early detection of the components of MS.